On love's gentle shore : a novel - Johnson, Liz, 1981- (Johnson, Liz, 1981- Prince Edward Island dreams, 2017)
"When Natalie O'Ryan returns to Prince Edward Island to plan her wedding, she runs into her childhood best friend--and discovers that the love she's been looking for is right where she left it"--